Value of green hydrogen when curtailed to provide grid balancing services. (5th October 2022) - Zenith, Federico; Flote, Martin Nord; Santos-Mugica, Maider; Duncan, Corey Scott; Mariani, Valerio; Marcantonini, Claudio
Abstract: This paper evaluates the potential of grid services in France, Italy, Norway and Spain to provide an alternative income for electrolysers producing hydrogen from wind power. Grid services are simulated with each country's data for 2017 for energy prices, grid services and wind power profiles from relevant wind parks. A novel metric is presented, the value of curtailed hydrogen, which is independent from several highly uncertain parameters such as electrolyser cost or hydrogen market price. Results indicate that grid services can monetise the unused spare capacity of electrolyser plants, improving their economy in the critical deployment phase. For most countries, up-regulation yields a value of curtailed hydrogen above 6 €/kg, over 3 times higher than the EU's 2030 price target (without incentives). However, countries with large hydro power resources such as Norway yield far lower results, below 2 €/kg. The value of curtailed hydrogen also decreases with hydrogen production, corresponding to the cases of symmetric and down-regulation. Highlights: Defined a metric independent of electrolyser cost or hydrogen price, which are a large source of uncertainty. Analysed the potential for grid services in multiple markets with real data for prices and wind power. Presented the separate contribution of grid services, spot prices and tariffs in the value of curtailed hydrogen.